PENGARUH PERUBAHAN PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH DR. MOEWARDI TERHADAP PEMANFAATAN LAHAN KOMERSIAL DI SEKITARNYA DI SURAKARTA - Nofa Yuniary; Murtanti Jani Rahayu; Rufia Andisetyana Putri (ARSITEKTURA, 2017)
Abstract: Rumah Sakit Umum Daerah Dr. Moewardi is a national scale-hospital provided by Central Java provincial government in the city of Surakarta. Assigned as a class hospital in 2007, Rumah Sakit Umum Daerah Dr. Moewardi led the citizen to have health service. The main activity of the district will be followed by the other development of the second activity. Hospital is one kind of main activities that can give impact to surrounding environment. Commercial activity area which is grow up around the hospital, such as boarding house, food court, convenience store and the other commercial services, gives impact to the sector’s revolution around the hospital. The issues in the research is the other utilization of the commercial area around the hospital which is effected by the change of health service of Rumah Sakit Umum Daerah Dr. Moewardi. This research aimed to find out the effect of Rumah Sakit Umum Daerah Dr. Moewardi’s health service  change to the utilization commercial area around the hospital. The method used is deductive-explanative descriptive analysis technique. The data collected is a real observation, respondent interview and document–based data. The result of the research shows that the service of Rumah Sakit Umum Daerah Dr. Moewardi is increasingly change by the years. It equals with the utilization of the commercial area around Rumah Sakit Umum Daerah Dr. Moewardi which is also increasing the commercial area so it can be concluded that the health service in Rumah Sakit Umum Daerah Dr. Moewardi gives impact to the utilization of commercial area around because both changes that increased. Keywords: development of health services, commercial land use change